REVITALIZATION OF DIGITAL PAI MEDIA: TECHNOLOGICAL LITERACY, TEACHERS' SOCIAL PRESENCE, AND STUDENTS' MOTIVATION FOR ACTIVE PARTICIPATION - Seituni, Siti; Isriyah, Mudafiatun (Sekolah Tinggi Agama Islam Al Hidayah, 2025)
Background: The rapid advancement of digital technology has transformed the landscape of education, including Islamic Religious Education (PAI), where traditional learning approaches are increasingly shifting toward digital platforms. However, the effectiveness of this transformation depends not only on the availability of technology but also on the ability of teachers and students to optimize its use for active and meaningful learning. Purpose: This study explores the revitalization of digital media in Islamic Religious Education (PAI) by examining the influence of technological literacy, teacher social presence, and student motivation on active participation in the digital learning environment. In the midst of the growing integration of technology in education, ensuring student engagement in PAI through effective media becomes increasingly essential. Method: A quantitative approach with a survey method was used, involving students from several Islamic schools who utilize digital platforms for learning. The data were analyzed using multiple regression to identify the contribution of each independent variable. Result: The findings reveal that technological literacy, teacher social presence, and student motivation significantly influence student participation. Among these, teacher social presence emerged as the strongest predictor. Conclusion: The study emphasizes the importance of pedagogical strategies that combine technological competence, emotional connection, and motivational support to foster meaningful student involvement in digital PAI learning.